Psychometric properties of the scale for the concrete love activity in a sample of young people in a Private University of Trujillo - Vera R., Nikolai (2012)
Following the line of research approach called "concrete love" (Rodas, 2011), it was proposed the following objectives: First, evaluate the psychometric properties of the scale on Concrete Love activity in a sample of young men and women who study in a private university in Trujillo. Second, describe the characteristics of love in those youths, comparing how it is distributed on gender and your relationship with age. It was found that the scale has acceptable characteristics of reliability and validity. On the other hand, the highest activity was compatibility and projectivity was the less activity developed. Itdid not find significant differences by gender, while age did not correlate significantly with love. Finally we discuss the results.